DIVERSITY OF BIRDS ACROSS LAND USE AND HABITAT GRADIENTS IN FORESTS, RUBBER AGROFORESTS AND RUBBER PLANTATIONS OF NORTH SUMATRA - Ayat, Asep; Tata, Hesti L. (Indonesian Journal of Forestry Research, 2015)
Birds play a pivotal role in the ecosystem, but in disturbed areas their roles may be limited due to the changes of their natural habitats. This paper studies the birds habitats in Simalungun and Asahan Districts, North Sumatra. The study was conducted in four habitats: natural forest, rubber agroforests, rubber monoculture plantations and emplacement areas. The birds were observed using descriptive survey methods by implementing a quick biodiversity survey, data were collected along one km transect.Â  The results showed that in total, 142 species of birds from 42 families were observed in the four habitats. Natural forests had the highest diversity of bird species, followed by rubber agroforests, emplacement areas and rubber plantations, with a Shannon-Wiener index of 3.8, 3.6, 3.0 and 2.9, respectively. Regarding the IUCN red list species, 12 bird species of near-threatened status and 2 species of vulnerable status were recorded.Â  Based on CITES categories, one species was listed in the Appendix I, 12 species were classified in Appendix II and 26 bird species were protected under Indonesian regulations. Changes in the structure and composition of the vegetation in disturbed forests and cleared land determined the richness of the bird species. The different tree compositions in the four habitats of the rubber estate plantations and surrounding areas influenced the number of bird species, bird diversity and species composition.